Literature Review: Hubungan Tingkat Depresi dengan Hipertensi pada Lansia - Ines Aulia; Farapti Farapti (Media Gizi Kesmas, 2024)
Background: Depression is one of the most common mental health problems faced by the elderly among many others. Depression, anxiety, and other negative emotions are important factors in the onset, development, and worsening of hypertension, which can make blood pressure fluctuations difficult to control, accelerate the course of the disease, and reduce the quality of life of hypertensive patients. Objectives: To determine the relationship between the level of depression and hypertension in the elderly. Methods: This study applied a literature review approach using various databases such as Pubmed, ScienceDirect, and Google Scholar. After the screening process, six journals relevant to the topic under investigation were found. Results: There were 6 articles that showed a significant association between depression and the incidence of hypertension in the elderly, highlighting the importance of taking psychological factors into account in their health management. Conclusions: It can be concluded that there is a relationship between depression and the incidence of hypertension in elderly.